2009
DOI: 10.1503/cmaj.081751
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous rectus sheath hematoma

Abstract: A 77-year-old woman was admitted to hospital with acute coronary syndrome and hypertensive crisis (i.e., a blood pressure of 210/110 mm Hg on admission). We administered acetylsalicylic acid, metoprolol and enoxaparin. One day later, after her blood pressure was stable and we had ruled out myocardial infarction, we performed an adenosine stress test. During the test, the patient became hypotensive and experienced nausea, confusion and abdominal pain.She had a blood pressure of 70/40 mm Hg and a heart rate of 6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0
2

Year Published

2011
2011
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 2 publications
0
4
0
2
Order By: Relevance
“…3 Spontan olarak, egzersiz sonrası ve Dengue ateşi gibi nadir hastalıklarda da görülebilmektedir. [4][5][6][7] Literatürde, laparoskopik hemikolektomi sonrası gelişen rektus kılıf hematomu da mevcuttur. 8 Tanı, klinik şüphe ve muayene bulguları ardından USG ve/veya bilgisayarlı tomografi (BT) ile konulabilir.…”
Section: Discussionunclassified
“…3 Spontan olarak, egzersiz sonrası ve Dengue ateşi gibi nadir hastalıklarda da görülebilmektedir. [4][5][6][7] Literatürde, laparoskopik hemikolektomi sonrası gelişen rektus kılıf hematomu da mevcuttur. 8 Tanı, klinik şüphe ve muayene bulguları ardından USG ve/veya bilgisayarlı tomografi (BT) ile konulabilir.…”
Section: Discussionunclassified
“…Como resultado de ello, se acumula sangre en la vaina del recto 1,2 . Dado que, en la mayoría de los casos, no hay una intervenció n quirú rgica previa, el proceso se denomina hematoma espontá neo de la vaina del recto (HEVR) 3 .…”
Section: Introducció Nunclassified
“…The risk is also greater with abdominal wall straining due to coughing or vomiting, in pregnancy, and in individuals taking other antiplatelet agents and/or anticoagulants. [5][6][7] We describe a fatal case of an 80-year-old female recently diagnosed with a cerebral infarction, who was undergoing LMWH therapy for pulmonary thromboembolism and deep vein thrombosis, and who presented with an acute palpable abdominal mass in hypovolemic shock. She was diagnosed with a large right abdominal wall hematoma.…”
mentioning
confidence: 99%
“…Other cases showed that a history of prior surgery, concomitant use of drugs such as antiplatelet or other anticoagulant agents in conjunction with LMWH, and renal failure could increase the risk of abdominal wall hematoma [1,5,6]. Straining the abdomen during processes such as coughing also increases the risk of hematoma formation,[5,6,7] as the abdominal wall muscles suddenly contract to increase intrathoracic pressure. Repeated damage during cough attacks in this present case probably led to the abdominal wall hematoma, which was aggravated by the LMWH.…”
mentioning
confidence: 99%